The influence of emitter resistance on the electrical parameters of mono- and multicrystalline silicon solar cells. Issue 3 (20th June 2019) - Swatowska, Barbara; Panek, Piotr; Michoń, Dagmara; Drygała, Aleksandra
Abstract : Purpose: The purpose of this study was the comparison and analysis of the electrical parameters of two kinds of silicon solar cells (mono- and multicrystalline) of different emitter resistance. Design/methodology/approach: By controlling of diffusion parameters, silicon mono- (Cz-Si) and multicrystalline (mc-Si) solar cells with different emitter resistance values were produced – 22 and 48 Ω /□. On the basis of current-voltage measurements of cells and contact resistance mapping, the properties of final solar cells based on two different materials were compared. Additionally, the influence of temperature on PV cells efficiency and open circuit voltage (Uoc ) were investigated. The PC1D simulation was useful to determine spectral dependence of external quantum efficiency of solar cells with different emitter resistance. The silicon solar cells of 25 cm 2 area and 240 µ m thickness were investigated. Findings: Considering the all stages of cell technology, the best structure is silicon solar cell with sheet resistance (Rsheet ) of 45-48 Ω /□. Producing of an emitter with this resistance allowed to obtain cells with a fill factor between 0.725 and 0.758, Uoc between 585 and 612 mV, short circuit current (Isc ) between 724 and 820 mA. Originality/value: Measurements and analysis confirmed that mono- and multicrystalline silicon solar cells with 48 Ω /□ emitter resistance have better parameters than cells with Rsheet of 22 Ω /□. The contact resistance is the highest for mc-Si with Rsheet of 48 Ω /□ and reaches the value 3.8 Ω cm.